2006
DOI: 10.1590/s1678-91992006000100012
|View full text |Cite
|
Sign up to set email alerts
|

Serological profile of anti-Toxoplasma gondii antibodies in apparently healthy dogs of the city of Botucatu, São Paulo State, Brazil

Abstract: Toxoplasmosis is a zoonosis caused byStatistically significant differences were not found regarding sex (32.2% male and 34.3% female reactors). Dogs without a defined breed showed seropositivity statistically higher than the pedigreed group. The occurrence of infection was considered higher with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
1
8

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 15 publications
(13 reference statements)
1
14
1
8
Order By: Relevance
“…In this study, although there was higher occurrence among 0-4.1-year-old animals (32.5%; CI95% 23.2-43.4%), followed by the intermediate age range (21.9; CI95% 14.0-32.7%), no significant association was detected in the analysis of either all three age ranges or each two ranges; differently from Langoni et al (2006), who observed higher occurrence among the oldest animals, 13.3-20 years (75%), and Da Silva et al (2009), who reported higher frequencies in age ranges above 6-8 years.…”
Section: Discussioncontrasting
confidence: 76%
See 4 more Smart Citations
“…In this study, although there was higher occurrence among 0-4.1-year-old animals (32.5%; CI95% 23.2-43.4%), followed by the intermediate age range (21.9; CI95% 14.0-32.7%), no significant association was detected in the analysis of either all three age ranges or each two ranges; differently from Langoni et al (2006), who observed higher occurrence among the oldest animals, 13.3-20 years (75%), and Da Silva et al (2009), who reported higher frequencies in age ranges above 6-8 years.…”
Section: Discussioncontrasting
confidence: 76%
“…In the present study, 25.4% of the tested samples were positive by IFAT and were within the State range from 19.7 to 33.1% (Brito et al 2002, Souza et al 2003, Langoni et al 2006) and the national range from 8.2 to 88.5% (Silva et al 1997, Souza et al 2003, Cañón-Franco et al 2004, Azevedo et al 2005, Romanelli et al 2007, Figueredo et al 2008, Da Silva et al 2009, Santos et al 2009 (Silva et al 1997, Brito et al 2002, Azevedo et al 2005, Langoni et al 2006, Dubey et al 2007b,c, Öncel et al 2007, Romanelli et al 2007, Da Silva et al 2009, Santos et al 2009). On the other hand, Cañón-Franco et al (2004) observed that most of the 76.4% seropositive dogs did not have low titers, ranging from 128 to 2048, which may indicate active infection.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations